(untitled) (Studia theodisca, 2022)
This paper intends to show how and to what extent the practices of postmemory (Hirsch) and “cumulative heroization” (Welzer), which are typical of the so-called generation of grandchildren in Germany, are embedded in Nora Krug’s graphic novel Heimat. Ein deutsches Familienalbum [Heimat. A German Family Album] (2018). It will be shown how these practices contribute to creating a work that in the end idealizes the German and family (Nazi) past rather than coming to terms with it, thus also reiterating a Germano-centric concept of Heimat.